PERSPEKTIF GILLES DELEUZE TERHADAP PROSES IMITASI DALAM MASYARAKAT KONSUMERIS DI ERA REVOLUSI INDUSTRI 4.0 - John Abraham Ziswan Suryosumunar (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
Revolution 4.0 signifies a condition when society has same dependency on digital technology, especially to access information and make communication with others. This condition encourages the easy distribution of various products into popular culture, both in the form of commodities and lifestyles. Imitation process occurs in the practice of community life with various stereotypes that are deliberately formed to attract people's interest to buying and owning. This paper based on the interpretation method seeks to use the perspective of a post-modern figure, Gilles Deleuze, with the concept of multiplicities to unravel the phenomena of the imitation process in consumerist society and its correlation with the development of digital technology in the industrial revolution era 4.0.